Stationary Organizer / Nor Fareha Zalhadi, Farah Nur Izzati Mohd Sazali and Umi Nazihah Jamal - Zalhadi, Nor Fareha; Mohd Sazali, Farah Nur Izzati; Jamal, Umi Nazihah (2021)
Recycle, reduce and reuse items is one of the solutions to overcome environmental problems. The concept of 3R can help to prevent any pollution from happening, reduce greenhouse gas emissions and global warming. A stationary organizer is an organizer that is made from boxes, newspapers, and bottles that are no longer used. The main reason for creating the stationery organizer from the reuse items is to reduce the energy that the manufacturer uses to extract the raw materials to make a new product. Other than that, it also can save our money from buying new organizers because we can create our organizer by using reuse items that we have. Therefore, this innovation is hoped to increase people's awareness to always reuse items that are no longer functioned like before and transform them into a new product that can benefit them.